POLA KONSUMSI: LITERASI EKONOMI, STATUS SOSIAL ORANG TUA DAN TEMAN SEBAYA - Filomina Nurjaya Onis; Lilik Sri Hariani; Ninik Indawati (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2018)
Consumption patterns can be influenced by the external factors and internal students. Several factors such as economic literacy, social statues parents, and the peers. Assuming that someone who has economic literacy tend to patterned consumption by smart which is to pattern of behavior rational, but economic literacy, social statues parents are very significant impact on consumption patterns, but those two factors group their peers also influences pattern of behavior consumption. This research intend to know influence in a partial and simultaneous between economic literacy, social statues parents and group their peers against consumption patterns graders XI social class high school of National Malang .This research uses the quantitative sample with the national high school students poor were 61 students data collection in this research that is using the survey, tests, interviews and documentation.